Recycled Leather and Sawdust Composite Sheets - Chaturvedi, D. K.; Sultan, Tipu (Transactions on Engineering and Computing Sciences, 2025)
This study explores the innovative combination of leather waste and sawdust with polyurethane (PU) to fabricate composite sheets. The utilization of leather waste and sawdust addresses the environmental concerns associated with their disposal while harnessing their potential as sustainable resources. The composite sheets offer a promising alternative to traditional materials, showcasing desirable properties such as enhanced durability, flexibility, and eco-friendliness. The abstract highlights the significance of this research in advancing sustainable material development and promoting circular economy principles. The present work provides immense potential for a new approach to make composite sheets by recycling of leather waste and sawdust to safeguard the environment and maintain ecology. This composite sheet can be a good substitute as a sustainable alternative to synthetic leather which affects the environment adversely.